PENGARUH UKURAN PERUSAHAAN, LEVERAGE, PROFITABILITAS, DAN SISTEM PENGENDALIAN INTERNAL TERHADAP AUDIT DELAY (STUDI EMPIRIS PADA PERUSAHAAN SUB SEKTOR PERTAMBANGAN BATUBARA YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2018) - Isnaini Hidayati; Anik Malikah; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2020)
ABSTRACTThe purpose of this research is to study the Effect of Firm Size, Leverage, Profitability, and Internal Control System on Audit Delay in listed coal mining sub sector companies on the Indonesian Stock Exchange (IDX) from 2016 to 2018. To analyze data using explanatory resource techniques using a quantitative approach. The population in this study is the coal mining sub sector companies listed on the Indonesian Stock Exchange period of 2016 to 2018, amounting to 27 companies. The sampling method using purposive sampling techniques and obtained 11 companies. The data analyze method of this study uses a linier multiple regression model. This study shows the result that Firm Size and Internal Control System do not affect the Audit Delay, while Leverage and Profitability affect the Audit Delay. Key word: Firm Size, Leverage, Profitability, Internal Control System, Audit Delay.